1930
DOI: 10.1042/bj0240250
|View full text |Cite
|
Sign up to set email alerts
|

Sulphur in organic and inorganic combination in pasture grasses

Abstract: THE sulphur content of pastures has recently become a subject of considerable importance both from the point of view of sulphur fertilisation of soils [Alway, 1927] and in relation to the sulphur requirements of sheep for wool-production [Robertson and Marston, 1928]. The question of sulphur deficiency in soils has led to very thorough surveys of the total sulphur content of pastures in different parts of the world, but the organic sulphur content of pastures has received little or no attention. Nevertheless t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1931
1931
1967
1967

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…This tendency was even more marked in 1954 and suggests that under conditions of ample sulphate supply, rye-grass absorbs the ion to a greater extent than the grasses in the other mixtures. There is a suggestion in the results of Aitken (1930) who analysed the leaf blades of several grass species in New Zealand and the figures quoted by Bosch (1954) that rye-grass has such a tendency. Strict comparisons between species made at identical stages of growth, however, are necessary before it may be concluded that rye-grass behaves in this way.…”
Section: Discussionmentioning
confidence: 96%
“…This tendency was even more marked in 1954 and suggests that under conditions of ample sulphate supply, rye-grass absorbs the ion to a greater extent than the grasses in the other mixtures. There is a suggestion in the results of Aitken (1930) who analysed the leaf blades of several grass species in New Zealand and the figures quoted by Bosch (1954) that rye-grass has such a tendency. Strict comparisons between species made at identical stages of growth, however, are necessary before it may be concluded that rye-grass behaves in this way.…”
Section: Discussionmentioning
confidence: 96%
“…The Sullivan colorimetric method showed that only a trace of cystine was present, although the addition of cystine to the hydrolysate proved the method to be applicable. 5. Further proof that pasture grass is deficient in cystine was obtained by determining the sulphide sulphur liberated on heating with 30 per cent, alkali.…”
Section: Sulphide Sulphurmentioning
confidence: 99%
“…In spite of the recognition of the problems associated with this method of separation, few alternatives have been proposed. Benzidine, which had been demonstrated to be the pre-eminent reagent for the determination of sulfate in plasma (Cuthbertson and Tompsett, 1931) and urine (Owen, 1936) did not find favor (Aitken, 1930) and was abandoned for use with plant extracts because of nonspecific precipitation which occurred (Wood and Barrien, 1939). A significant advance was made when Johnson and Nishita (1952), making use of the reaction by which sulfate may be reduced to sulfide, then to be converted to methylene blue (Gustafsson, 1960), developed a method for the direct determination of low concentrations of sulfate sulfur in plant material.…”
mentioning
confidence: 97%